STRENGTHENING E-BRANDING STRATEGY OF SHARIA HOTEL IN INDONESIAN HOTEL INDUSTRY - Eska Nia Sarinastiti; Uljanatunnisa Uljanatunnisa (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2020)
Purpose: This research is expected to be able to identify and analyze the strengthening of e-branding strategies of Sharia Hotels in the Indonesian hotel industry. Research methods: This study uses qualitative research with data collection techniques through semi-structured interviews, observation, and documentation. Results and discussions: The results of the research show, firstly, hotel with Islamic nuances according to the MUI Sharia Hotels including Hilal 2 which is a management and operational manner have rigid rules that must comply with Islamic rules, while Muslim Friendly Hotels include Hilal 1; secondly, strengthening the Sharia Hotel e-branding strategy including 1) strengthening domain names, brand identity, and web design; 2) partnership with various online travel agents; 3) installation of advertising and promotion media; 4) strengthening interaction through social media networks; the third is related to the challenges in e-branding of Sharia Hotels, it is the perception of the Indonesian people whose Muslim majority religion does not need differentiation in Sharia Hotels with Muslim Friendly Hotels and the perception that Sharia Hotels only accept Muslim tourists even though Sharia Hotels accept tourists universally like Conventional Hotels. Conclusion: Effective e-branding through online media in the Sharia hotel industry, it is proven can build a positive image and not only Muslim tourists who have known sharia hotels, but some non-Muslim tourists also have brand awareness in the existence of Sharia Hotel